Repeated Measures Analysis of Alcohol Patterns among Gay and Bisexual Men in the Momentum Health Study. (16th April 2018) - Roth, Eric Abella; Cui, Zishan; Rich, Ashleigh; Lachowsky, Nathan; Sereda, Paul; Card, Kiffer; Moore, David; Hogg, Robert
ABSTRACT: Background : This study analyzed repeated study visits (n = 2, 624) of 693 gay and bisexual men (GBM) in the Momentum Health Study from July, 2012 to June, 2015. Based on recent cross-sectional analyses, we hypothesized that over the study period: (1) hazardous drinking levels would remain high, (2) GBM classified as Hazardous Drinkers will be consistently associated with high risk sex, and (3) GBM classified as Always Hazardous Drinkers differ significantly from Sometimes Hazardous Drinkers. Methods : AUDIT classified participants as Non-Hazardous Drinkers or Hazardous Drinkers, the Cochran–Mantel–Haenszel Test assessed hazardous drinking trends, and Generalized Estimating Equations (GEE) analysis identified Hazardous Drinking covariates. Logistic regression analysis of participants with at least two study visits (575) compared those who were Sometimes Hazardous Drinkers (n = 171) with Always Hazardous Drinkers (n = 129). Results : At baseline 40% of participants were Hazardous Drinkers, but there was a significant decline in hazardous drinking by visit and Hazardous Drinkers were not significantly associated with high risk sex. Always Hazardous Drinkers had significantly more high risk sex and gay bar attendance, but less often sought Internet sex partners compared to Sometimes Hazardous Drinkers. Conclusions : Analyses did not support the first two hypotheses, but distinguishing between Always and Sometimes Hazardous drinkers identified a young GBM subgroup associated with significantly higher levels of high risk sex and social support measures. These results suggest interventions programs based on Social Norms Theory, which predicts peer norms among youth are important factors in regulating drinking patterns, may be effective for these men.